2002
DOI: 10.1038/sj.jhh.1001415
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in ethanol metabolizing enzymes and blood pressure in Japanese alcohol consumers

Abstract: Orientals have unique genetic polymorphisms in ethanol metabolizing enzymes, such as alcohol dehydrogenase-2 (ADH2), aldehyde dehydrogenase-2 (ALDH2) and cytochrome P450-2E1 (CYP2E1). Of the three studies conducted to clarify the influence of ALDH2 genotypes on sensitivity to the pressor effects of alcohol in Japanese, only one was suggested, though indirectly, higher sensitivity in drinkers having the genotype of inactive ALDH2. This discrepancy prompted us to determine ADH2, ALDH2 and CYP2E1 genotypes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
2
19
1
2
Order By: Relevance
“…From these results, it can be concluded that acetaldehyde accumulates even in moderate alcohol consumers irrespective of ALDH2 and CYP2E1 genotypes, and that neither those genotypes nor urinary acetaldehyde affects common health consequences related to moderate alcohol consumption. A possible etiological role of ALDH2 deficiency and consequent high blood acetaldehyde in alcohol-related hypertension has been suggested by Itoh et al (1997), but effects of ALDH2 genotypes on the alcohol-blood pressure relationship have been ruled out in many studies (Okayama et al 1994;Tsuritani et al 1995;Tanaka et al 1997;Takagi et al 2001;Amamoto et al 2002;Yamada et al 2002), similar to the present results. A high incidence of myocardial infarction in those having ALDH2 deficiency has been demonstrated to be a reflection of the low serum HDLc due to low alcohol consumption (Takagi et al 2002).…”
Section: Discussionsupporting
confidence: 87%
“…From these results, it can be concluded that acetaldehyde accumulates even in moderate alcohol consumers irrespective of ALDH2 and CYP2E1 genotypes, and that neither those genotypes nor urinary acetaldehyde affects common health consequences related to moderate alcohol consumption. A possible etiological role of ALDH2 deficiency and consequent high blood acetaldehyde in alcohol-related hypertension has been suggested by Itoh et al (1997), but effects of ALDH2 genotypes on the alcohol-blood pressure relationship have been ruled out in many studies (Okayama et al 1994;Tsuritani et al 1995;Tanaka et al 1997;Takagi et al 2001;Amamoto et al 2002;Yamada et al 2002), similar to the present results. A high incidence of myocardial infarction in those having ALDH2 deficiency has been demonstrated to be a reflection of the low serum HDLc due to low alcohol consumption (Takagi et al 2002).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the ALDH2 genetic polymorphism was also significantly associated with alcohol consumption and influenced the risk of CAD. Fourth, ALDH2 genetic polymorphism may increase blood pressure, influencing the risk of CAD (Yamada et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the influence of rs671 genotypes on blood pressure. 11,[15][16][17] Almost all earlier studies, except for the one by Itoh et al, have reported that ALDH2 rs671 cannot significantly influence the alcohol-blood pressure relationship. 18 The following reasons may account for discrepancies between the results of our study and those of others: (1) sample size is relatively small in other studies; (2) physiological, aging-related blood pressure elevation is not negligible when the average age of the participants is relatively high in some studies; (3) the confounding pressor effects of the amounts of alcohol consumption may not be sufficiently adjusted for by multivariate analysis alone using the entire study population; and (4) nondrinkers should be excluded from the analysis to evaluate 'gene-environment (that is, alcohol intake in this case) interaction.…”
Section: Alcohol Metabolizing Enzymes and Blood Pressure M Tsuchihashmentioning
confidence: 99%